Self Efficacy Pencegahan Komplikasi pada Penderita Hipertensi Emergensi di Kelurahan Gunung Sekar - Andayani, Qurnia; Kuzzairi, Kuzzairi; Widari, Sri (Politeknik Negeri Madura, 2023)
Emergency hypertensive patients need self-awareness of their disease to prevent complications, one of which is stroke which can cause death. This study aims to determine self-efficacy in preventing complications in hypertensive emergencies. This research is a type of cross sectional research. The population in this study were 28 hypertensive emergencies in the Gunung Sekar Village, Sampang District, using the probability-total population sampling technique. This study uses one variable, namely self-efficacy in preventing complications. The research was conducted in Gunung Sekar Village, Sampang District on 15 February 2023 - 04 March 2023. Data collection was carried out by providing a closed ended-likert scale questionnaire with a total of 12 questions and then data processing was carried out in the form of editing, scoring, coding, tabulating, interpreting . Most of the respondents in Gunung Sekar Village had low self-efficacy in preventing complications, as many as 16 people (57%), while almost half of the respondents had a high level of self-efficacy (43%). Most of the hypertensive emergencies in Gunung Sekar Village have low self-efficacy in preventing complications, therefore health workers should provide more intensive counseling about prevention of complications in hypertensive emergencies so that the more knowledge the respondents have, it is hoped that they will be more confident in prevent complications.